PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP PRESTASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI PT. PELNI CABANG PARE-PARE - Anwar, Aqilla Marwa; Kadir, Muh Akob; Hasbiyadi, Hasbiyadi (Gapenas Publisher, 2024)
The Influence of Work Discipline and Work Stress on Work Performance with Job Satisfaction as an Intervening Variable at PT. PELNI Pare-Pare Branch. (supervised by Muh Akob Kadir and Hasbiyadi). This study aims to determine the direct influence of work discipline, work stress and job satisfaction on work performance. The direct influence of work discipline and work stress on job satisfaction. The indirect influence of work discipline and work stress variables on work performance with job satisfaction as an intervening variable at PT. PELNI Pare-Pare Branch. Data collection using primary data obtained from questionnaires using saturated samples. The population in this study was 44 respondents. The results of the questionnaire have been tested for validity and reliability using the PLS model scheme and model evaluation, inner model evaluation with determinant coefficient tests, model goodness of fit tests and hypothesis tests both directly and indirectly. The results of this data processing use SmartPLS version 3.0. The results of the study directly show that the variables of work discipline, work stress and job satisfaction have a positive and significant effect on work performance. Work discipline and work stress have a positive and significant effect on work satisfaction. The results of the study indirectly show that work discipline does not affect work performance with work satisfaction as an intervening variable and work stress has a positive and significant effect on work performance with work satisfaction as an intervening variable